2022
DOI: 10.3389/fonc.2022.1000056
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on diagnosis and treatment of patients with soft tissue and bone sarcomas or aggressive benign musculoskeletal diseases: A single-center retrospective study (SarCorD study)

Abstract: BackgroundThe COVID-19 pandemic led to a rapid reorganization of healthcare activities, leading to reduced access to clinics, interruption of screenings, and treatment schedule modifications in several cancer types. Few data are available on sarcomas. We analyzed COVID-19-related diagnostic delay in a sarcoma referral center in Italy.MethodsWe retrospectively enrolled in this study patients with histological diagnosis of soft tissue or bone sarcoma and aggressive benign musculoskeletal diseases obtained during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…[ 16 ] Onesti et al observed a diagnostic delay in soft tissue or bone sarcomas with a median time from the first symptom to the definitive histological diagnosis. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Onesti et al observed a diagnostic delay in soft tissue or bone sarcomas with a median time from the first symptom to the definitive histological diagnosis. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…9 In a single-center study conducted in Rome, our Italian colleagues revealed, in a cohort of 372 patients, a significant increase in the time of diagnosis (from 90 to 103 days) without a significant increase in the time to treatment (from 144 to 151 days). 10 Lastly, an international multicenter study stressed that stringent lockdown was associated with a major decrease in cancer surgeries such as sarcoma surgery (413 newly diagnosed sarcoma, odds ratio 0.67 (95% CI: .59–0.67) for non-surgical management during stringent lockdown). 11 In France, during the first pandemic year, there were two stringent lockdowns (17 March–11 May 2020 and 30 October–15 December).…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study including a larger sample of 372 patients with bone sarcomas and soft tissue sarcomas (STS) confirmed this delay until a definitive histologic diagnosis before and after the pandemic (90 versus 103 days, respectively, p-value: 0.024). However, no statistically significant differences were observed in terms of the stage at diagnosis, progression-free survival (PFS) and overall survival (OS) between the COVID-19 arm and the control arm [28].…”
Section: Telemedicine and Sarcoma Diagnosismentioning
confidence: 99%
“…However, regarding the implementation of telehealth in psychological support, there are certain problems needed to be addressed, pertaining to the unique characteristics of ma-lignancies under therapy [76]. For example, sarcomas as unique entities require a more detailed approach that is tailored to the patient's individualized needs [28].…”
Section: Telerehabilitation For Sarcoma Patientsmentioning
confidence: 99%